Методические погрешности определения параметров антенн амплитудными методами - Пятайкин, М. И.; Усина, А. В. (Weber, 2010)
Methodical errors of amplitude methods of antennas parameters determination under using harmonically signal was examined.
Keywords: определение параметров антенн; погрешности определения параметров